Editorial and Production Credits (Vol. 1, No. 1, Autumn 2011) - of Academic Writing, Journal (Journal of Academic Writing, 2011)
This document provides editorial and production credits for the Journal of Academic Writing Vol. 1, No. 1, Autumn 2011.